A global province? : the development of a movie culture in a small provincial city 1919-1945 : a thesis presented in partial fulfillment of the requirements for the degree of Master of Arts in History at Massey University - Knuckey, Pauline (Massey University, 2012)
Abstract not available.
Keywords: Motion pictures; Feature films; Movies; New Zealand; Nationalism in motion pictures; Popular culture; Palmerston North; Social life and customs